(untitled) (Journal of NELTA, 2011)
This article discusses how mother-tongue interference can influence second or forreign language learning, specifically learning English. In Nepal not only does the mother tongue interfere with English learning, but also the methods used in the schools, specifically the grammar translation method and the deductive approach to teaching grammar, influence student learning as well. Key words: Tertiary level; Inductive approach; Deductive approach; Fossilization; Language transfer Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 109-109 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4615